Penerapan Model Pembelajaran Number Head Together (NHT) Terhadap Peningkatan Hasil Belajar Siswa Kelas X Dalam Mata Pelajaran Dasar-Dasar Desain Grafis Di SMK Negeri 1 Takalar - Nurkhatima, Riswani; Lamada, Mustari M.; Riska, Muhammad (Jurnal Komputer Indonesia, 2024)
This study aims to determine the improvement of student learning outcomes through the application of the Number Head Together (NHT) learning model in class X SMK Negeri 1 Takalar. This research is included in the type of Classroom Action Research (PTK). The research subjects in this thesis are students of class X TKJ 01 at SMK Negeri 1 Takalar. The research was conducted in two cycles, where each cycle consisted of two meetings so that there were a total of four meetings in this study. Data collection techniques used by researchers include observation, Pretest-Posttest tests, questionnaires, and documentation. The data analysis applied was qualitative descriptive analysis using the percentage method to process the data that had been collected. Based on the findings and analysis of research data, it can be concluded that the application of the Number Head Together (NHT) learning model has a positive impact on student learning outcomes. Information was obtained that before the action was taken, the percentage of learning completeness was 28%, including 9 people. After implementing learning in cycle I by applying the Number Head Together method, there was an increase in percentage to 62.5%, involving 20 people. In cycle II, the percentage of learning completeness reached 93.75%, involving 30 people. Based on students' responses to the use of the Number Head Together learning model, it was concluded that out of a total of 32 respondents, 30 people or 94% stated that they were very satisfied, while 2 people or 6% stated that they were satisfied. There were no respondents who gave unfavourable, unfavourable or very unfavourable ratings, so it can be concluded that overall, respondents were very satisfied in using the Number Head Together (NHT) learning model in the learning process. Translated with DeepL.com (free version)